2010
DOI: 10.1029/2009jd013250
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime chemical evolution of aerosol and trace gases in a power plant plume: Implications for secondary organic nitrate and organosulfate aerosol formation, NO3 radical chemistry, and N2O5 heterogeneous hydrolysis

Abstract: [1] Nighttime chemical evolution of aerosol and trace gases in a coal-fired power plant plume was monitored with the Department of Energy Grumman Gulfstream-1 aircraft during the 2002 New England Air Quality Study field campaign. Quasi-Lagrangian sampling in the plume at increasing downwind distances and processing times was guided by a constant-volume balloon that was released near the power plant at sunset. While no evidence of fly ash particles was found, concentrations of particulate organics, sulfate, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 119 publications
2
78
2
Order By: Relevance
“…NO 2 photolysis at 405 nm and shorter wavelengths prevents direct measurement of path extinction = photoacoustic absorption since some of the absorbed optical power goes into bond breaking rather than to heat. O 2 has been investigated as a calibration gas in the oxygen A band spectral region near 760 nm (oxygen A band, tunable laser) but in this wavelength range, gaseous light absorption involves significant relaxation processes that are mediated by water vapor (Gilles et al, 2010;Tian et al, 2009). In this case, the molecular physics of oxygen is very interesting, but the accuracy of using gas calibration for aerosol light absorption measurement is less assured.…”
Section: Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…NO 2 photolysis at 405 nm and shorter wavelengths prevents direct measurement of path extinction = photoacoustic absorption since some of the absorbed optical power goes into bond breaking rather than to heat. O 2 has been investigated as a calibration gas in the oxygen A band spectral region near 760 nm (oxygen A band, tunable laser) but in this wavelength range, gaseous light absorption involves significant relaxation processes that are mediated by water vapor (Gilles et al, 2010;Tian et al, 2009). In this case, the molecular physics of oxygen is very interesting, but the accuracy of using gas calibration for aerosol light absorption measurement is less assured.…”
Section: Calibrationmentioning
confidence: 99%
“…Jacobson (1999) found that the nearly 50 % decline in UV radiation within the boundary layer (BL) in Los Angles was due to substantial UV absorption by nitrated and aromatic aerosols and gaseous species. A very recent study indicated nighttime formation of particulate organic nitrate and organosulfate species in coal-fired power plant plumes (Zaveri et al, 2010) that may also absorb UV radiation the following day.…”
Section: Introductionmentioning
confidence: 99%
“…Similar free-floating balloons have been used for many years to characterize transport and measure trajectories (e.g., Lally, 1967;Banta, 1976;Zak, 1983;Malaterre, 1993;Knudsen and Carver, 1994;Stohl, 1998;Businger et al, 1999;Johnson et al, 2000;Riddle et al, 2006;Mao et al, 2006;Zaveri et al, 2010a, b). These efforts have generally focused on tracking the horizontal motion of air masses or equivalently volumes of air that are sufficiently large to maintain their physical and chemical identity over a time period of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these model predictions, direct measurements of particle-phase ON concentrations in both laboratory and ambient studies are scarce due to limitations of measuring techniques and ON concentrations often must be inferred. For example, Zaveri et al (2010) inferred up to ∼0.4 µg m −3 of particulate ON (corresponding to <5% of total particulate mass) in a nocturnal power plant plume based on particle acidity and gasparticle equilibrium analysis of Aerodyne quadrupole aerosol mass spectrometer (Q-AMS) measurements. While aerosol mass spectroscopy is the most commonly employed technique for measuring the chemical composition of OM, it is not ideal for directly measuring ON concentrations (Farmer et al 2010).…”
Section: Introductionmentioning
confidence: 99%